Cocoa fresh beans aqueous extract as free radical quencher and ferric reducer. - Kian Chee, Samuel Yap; MD Yusof, Arief Huzaimi Bin; Chin, Hui Han (Indonesian Coffee and Cocoa Research Institute, 2022)
The presence of free radicals and oxidants in our body is either produced by our body through normal cell metabolisms or from environment surrounding us such as radiation, medication, pollutants or others. The free radicals and oxidants can be harmful to our body when their accumulation posing oxidative stress in the body. Cocoa beans are rich in polyphenols, which are functioning as antioxidant. However, each antioxidant has difference response towards either free radicals or other oxidants. The purpose of this research was to study the ability of cocoa fresh beans aqueous extract functions as antioxidant between its ability to reduce ferric to ferrous and number of free radicals removed from organic chemical compound of 2,2-diphenyl-1-picrylhydrazyl (DPPH). A series concentration of cocoa fresh beans aqueous were prepared. Its ability as ferric reducer was determined based on ferric reducing antioxidant power (FRAP) assays and its ability as free radicals scavenger was determined using DPPH assays. This study revealed that freeze dried cocoa fresh beans aqueous extract of 50 ppm was able to reduce 3.2 x 10 15 of ferric molecules to ferrous. Concentration below 20 ppm generally was not able to reduce Fe(III) to Fe(II). Whereas, at concentration of 45 ppm freeze dried cocoa fresh beans aqueous extract was estimated able to remove 1.4 x 10 17 organic nitrogen free radicals from DPPH assay. This study suggests that freeze dried cocoa fresh beans aqueous extract has better performance in quenching free radicals compared to reducing ferric into ferrous.